PROSPECTS FOR RAISING EFFICIENCY OF POSTOPERATIVE ANESTHESIA DURING NEURAXIAL BLOCK (REVIEW OF LITERATURE) - A. V. Zharnikov (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
This article presents the literature data on existing methods of postoperative pain relief. The technique of extended micro-catheter postoperative analgesia is discussed, as well as advantages and disadvantages of the method. Described method of microencapsulation is used to prolong the action of drugs, in particular local anesthetics. The effectiveness of encapsulated 2% lidocaine and bupivacaine was experimentally proven. The research showed that structural components of liposomes, liposomes themselves and liposomal drugs have clear pharmacological effects, which is superior to their conventional forms. Liposomal membranes protect drugs from preterm metabolism, alter pharmacokinetics and pharmacodynamics that allow to greatly reduce the applicable doses, enhance the action and to reduce high toxicity of administered drugs. Liposomal forms of directed drug transport cross the blood-brain barrier, cell membrane and subcellular structures, which allows to recommend them for anesthesiological purposes, for treatment of cancer, infectious diseases, cardiac, neurological diseases, gene therapy, and many diseases that were previously resistant to classical pharmacotherapy. The study of epidural anesthesia with the use of liposomal bupivacaine for postoperative analgesia in cancer patients demonstrated that duration of drug action increased 2-3 times in comparison with conventional bupivacaine. There are on-going studies of liposomal drugs, filled with local anesthetics as a possible method of adequate postoperative analgesia and control of pain in the postoperative period.